Gremlin1 promotes carcinogenesis of glioma in vitro. (February 2017) - Guan, Yongchang; Cheng, Wen; Zou, Cunyi; Wang, Tingzhong; Cao, Zhi
Summary: As the most prevalent and lethal type of brain tumours, gliomas, especially malignant ones, are relatively resistant to conventional therapies. Gremlin 1 (GREM1) is a secreted glycoprotein that is implicated in the maintenance of cancer stem cells in tumour hierarchy. In the current study, the role of GREM1 in the carcinogenesis of glioma was studied using a knockdown approach. We first examined the expression level of GREM1 in the clinical samples, and then evaluated the effect of GREM1 knockdown on the viability and colony formation capacity of U87‐MG cells. Moreover, the migration ability, invasiveness, cell cycle, and apoptosis of GREM1 ‐silenced cells were assessed. Furthermore, the involvement of functional GREM1 in the epithelial‐mesenchymal transition (EMT) process of glioma was investigated by detecting the expression levels of glioma‐associated oncogene homologue 3 (GLI3) and EMT‐related molecules. Our results demonstrated that knockdown of GREM1 reduced cell viability, suppressed migration and invasion, and inhibited GLI3 expression and the EMT process in U87‐MG cells. Meanwhile, GREM1 silencing promoted apoptosis in U87‐MG cells through the accumulation of Bax, cleaved caspase‐3, and cleaved poly (ADP‐ribose) polymerase (PARP) as well as the downregulation of Bcl‐2. In addition, GREM1 knockdown abolished transforming growth factor (TGF)‐β1‐mediated activation of the Smad pathway, which may underlie the mechanism of GREM1‐regulated EMT. In conclusion, GREM1 plays an important role in the development of glioma, and it may serve as a potential target in glioma therapy.